A FORMALISATION APPROACH FOR COLLABORATIVE USER EXPERIENCE DESIGN. (May 2020) - Kerpen, D.; Conrad, J.; Wallach, D.
Abstract: We propose to combine Collaborative User Experience Design (CUXD) projects with the integrated product and process modelling theory CPM/PDD to formalise the CUXD process model. CPM/PDD is discussed as a Design Theory and Methodology (DTM) to describe a product as well as the product development process based on a clear distinction of characteristics and properties. CUXD is presented as a cross-disciplinary, human-centred development model. It focuses on team collaboration, relates to concepts of Design Thinking, Agile Development as well as Lean UX and it highlights user experience metrics.